2013
DOI: 10.4049/jimmunol.1202891
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of Global CD4+ Subset Dysfunction Is Associated with Spontaneous Clinical Resolution of Pulmonary Sarcoidosis

Abstract: Sarcoidosis pathogenesis is characterized by peripheral anergy and an exaggerated, pulmonary CD4+ Th1 response. In this study, we demonstrate that CD4+ anergic responses to polyclonal TCR stimulation are present peripherally and within the lungs of sarcoid patients. Consistent with prior observations, spontaneous release of IL-2 was noted in sarcoidosis bronchoalveolar lavage CD4+ T cells. However, in contrast to spontaneous hyperactive responses reported previously, the cells displayed anergic responses to po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
94
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(99 citation statements)
references
References 43 publications
3
94
1
Order By: Relevance
“…Our analyses were adjusted for lymphocyte counts, as lymphopenia may be seen in sarcoidosis [2]. In future studies, we propose to perform cell sorting analyses of T-cell subsets to ascertain whether these findings stemmed from peripheral changes in differential subsets of lymphocytes in sarcoidosis; however, a recent study by OSWALD-RICHTER et al [35] showed that sarcoidosis peripheral and BAL sorted CD4 + T-cells exhibited decreases in the TCR-responsive genes LCK and PKCQ, both of which were also shown to be downregulated in our Ingenuity TCR signalling pathway analyses. Our results add to their study by demonstrating that the degree of TCR downregulation has important clinical correlations longitudinally.…”
Section: Discussionmentioning
confidence: 99%
“…Our analyses were adjusted for lymphocyte counts, as lymphopenia may be seen in sarcoidosis [2]. In future studies, we propose to perform cell sorting analyses of T-cell subsets to ascertain whether these findings stemmed from peripheral changes in differential subsets of lymphocytes in sarcoidosis; however, a recent study by OSWALD-RICHTER et al [35] showed that sarcoidosis peripheral and BAL sorted CD4 + T-cells exhibited decreases in the TCR-responsive genes LCK and PKCQ, both of which were also shown to be downregulated in our Ingenuity TCR signalling pathway analyses. Our results add to their study by demonstrating that the degree of TCR downregulation has important clinical correlations longitudinally.…”
Section: Discussionmentioning
confidence: 99%
“…1 T cells exhibit reduced proliferative capacity upon TCR stimulation, compared with healthy controls (1,2). It was also noted that blockade of the PD-1 pathway restored proliferative capacity in sarcoidosis CD4 1 T cells (1).…”
Section: Sarcoidosis Cd4mentioning
confidence: 96%
“…This cut off was based upon prior publications demonstrating proliferative capacities of less than 50% with sarcoidosis disease severity (1,2). Participant demographics are outlined in Table 1.…”
Section: Study Populationmentioning
confidence: 99%
See 2 more Smart Citations